FACILITATING INTERPRETIVE RESILIENCE: - G O West (Acta Theologica)
This article argues that the notion of the Bible as a site of struggle offers resources that may facilitate interpretive resilience for communities/sectors that have been marginalised by dominant biblical theologies. While the notion of the Bible as a site of struggle had its conceptualisation within historical-critical redaction criticism, literary-narrative and literary-rhetorical criticisms provide similar kinds of “critical” recognition of ideo-theological contestation within the biblical text, whether the final form or a socio-historically reconstructed redactional edition. This article uses the Joseph story in Genesis as a case study. Central to the understanding of interpretive resilience in this article is the recognition that marginalised sectors themselves build their interpretive resilience as they navigate and negotiate the (additional) kinds of resources biblical studies might offer.